Business Capital and Product Innovation as Determinants of MSME Financial Performance in Medan Labuhan District - Edisah Putra Nainggolan; Syarla Mauza Calista (Lembaga Riset Ilmiah, 2026)
his study aims to analyze the influence of business capital and product innovation on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Medan Labuhan District. The research uses a quantitative approach with a survey method. Primary data was collected through the distribution of questionnaires to 81 MSME actors engaged in the culinary, trade, and service sectors. The data analysis technique used is Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS application. The results of the study show that business capital has a positive and significant effect on the financial performance of MSMEs with a path coefficient of 0.236 and a p-value of 0.000. In addition, product innovation also has a positive and significant effect on the financial performance of MSMEs with a path coefficient of 0.417 and a p-value of 0.000. These findings indicate that increasing business capital and the ability to innovate in product development can improve the financial performance of MSMEs. Product innovation has been proven to have a greater influence than business capital in encouraging improvement in financial performance. This research provides an implication that MSME actors need to improve business capital management and innovate products in a sustainable manner to strengthen competitiveness and achieve sustainable business growth.